Application of Axiological Values in Character-Based Education Management - Retnowati, Ambar; Rumlinda, Rumlinda; Lestari, Fitriana Ika; Surachmi, Sri; Ratnasari, Yuni (Widyagogik, 2025)
Education management is strategically important not only for cognitive transfer but also for cultivating students' moral character, especially in addressing current educational practices that often overlook the axiological dimension (values related to goodness, ethics, and humanity). This study aims (1) to comprehensively describe the form and role of axiological values in character-based education management; (2) to analyze the application of these values in managerial practices, including policy planning, implementation, and evaluation; and (3) to formulate a conceptual model for the sustainable application of axiological values to strengthen character-based education management. This research employed a qualitative method with a descriptive-philosophical approach to profoundly understand the relationship between values, morals, and educational managerial practices. Data were collected through in-depth interviews, observation, documentation study, and literature review. The findings indicate that the application of axiological values encompasses three core domains: the institutional value foundation (e.g., religiosity, honesty, responsibility), managerial implementation (e.g., democratic and humanistic leadership), and the formation of a character-based organizational culture (inclusive and collaborative). Philosophical reflection confirms that these values serve as an ethical compass in managerial decision-making, enhancing individual morality and strengthening institutional effectiveness. In conclusion, the research confirms the strategic importance of integrating axiological values to create a system that is not only functionally effective but also humanistic, moral, and sustainable, contributing a conceptual model for future education development.